Afro-Asian colonization: Should Europeans repent for an ongoing third world underdevelopment? - Karim, A.H.M Zehadul (2015)
European colonization in Asia and Africa in the past had fully destroyed the economy and culture of those continents in various ways. It is evidenced that the economic resources of many colonial countries of Asia, Africa as well as Latin America were extracted unscrupulously for the benefit of the Europeans who had simultaneously oppressed the people of these continents to secure their wealth and resources. As a matter of fact, the merciless subjugation of the colonial powers initially began with the destruction of agriculture when the Europeans compelled many of the farmers of these colonial countries to forcibly abandon producing their food crops and instead, compelled them to go for cash crop production. This eventually contributed to the development of a European infrastructure which benefitted and glorified their nations with enormous economic development.